Abundant serendipitous emission line sources with JWST/NIRSpec. Issue 3 (27th March 2019) - Maseda, Michael V; Franx, Marijn; Chevallard, Jacopo; Curtis-Lake, Emma
Abstract: The James Webb Space Telescope will provide observational capabilities that far exceed those of current ground- or space-based instrumentation. In particular, the Near-Infrared Spectrograph (NIRSpec) instrument will take highly sensitive spectroscopic data for hundreds of objects simultaneously from 0.6 to 5.3 μ m. Current photometric observations suggest a large and increasing number of faint ( M UV > −16) galaxies at high redshift, with increasing evidence that galaxies at these redshifts have optical emission lines with extremely high equivalent widths. A simple model of their emission line fluxes and number density evolution with redshift is used to predict the number of galaxies that NIRSpec will serendipitously observe during normal observations with the microshutter array. At exposure times of ≈20 h in the low-resolution prism mode, the model predicts that, on average, every open 1 × 3 'microslit' will contain an un-targeted galaxy with a detectable [O iii ] and/or H α emission line; while most of these detections are predicted to be of [O iii ], H α detections alone would still number 0.56 per open 'microslit' for this exposure time. Many of these objects are spectroscopically detectable even when they are fainter than current photometric limits and/or their flux centroids lie outside of the open microshutter area. The predicted number counts for such galaxies match z ∼ 2 observations of [O iii ] emitters from slitless grism spectroscopic surveys, as well as theoretical predictions based on sophisticated modelling of galaxy spectral energy distributions. These serendipitous detections could provide the largest numbers of z > 6 spectroscopic confirmations in the deepest NIRSpec surveys.